The Transformative Role of Interactive Narratives in Contemporary Art and Culture - Handaru, Wuri Cahya (Harmonia : Journal of Music and Arts, 2025)
Cross-media storytelling has emerged as a pivotal practice in contemporary art and digital culture, redefining the boundaries of narrative creation and audience engagement. This review aims to synthesize existing literature on interactive narratives, focusing on how multimodality, interactivity, and participatory cultures reshape storytelling practices. A systematic literature review was conducted across Scopus, Web of Science, and Google Scholar, using targeted keywords to capture relevant studies, with inclusion criteria emphasizing cross-media narratives, audience engagement, and digital artistic practices. Findings reveal that interactive and multimodal approaches foster deeper audience immersion, enhancing memory retention and emotional connection, while digital platforms and participatory practices democratize authorship and support collaborative storytelling. Cross-cultural examples demonstrate how storytelling functions as a negotiation tool for identity and cultural heritage, while educational applications highlight its effectiveness in improving learning outcomes. Immersive technologies, particularly AR, VR, and AI, expand narrative experiences but also pose ethical challenges concerning authenticity, authorship, and misinformation. Systemic factors such as infrastructure, policy frameworks, and technology access critically shape the reach and inclusivity of these narratives. The review underscores the urgency of addressing methodological, ethical, and systemic barriers, recommending expanded infrastructure investment, supportive regulations, and interdisciplinary research. These strategies are vital for advancing cross-media storytelling as a transformative force in cultural dialogue, education, and creative innovation.